Viability and functional impact of probiotic and starter cultures in salami-type fermented meat products - Mani-López, Emma; Hernández-Figueroa, Ricardo H.; López-Malo, Aurelio; Morales-Camacho, Jocksan I. (Frontiers in Chemistry, 2024)
Salami, a well-known fermented meat product, is made from selected ground meat mixed with curing agents and spices. This work aimed to determine the viability of Lactiplantibacillus plantarum (as a starter), Lactobacillus acidophilus (probiotic microorganism), and their mixture during the fermentation and ripening of a salami-type product, evaluate the microbiological and physicochemical changes and assess the sensory acceptability of the final product. L. acidophilus has not been sufficiently explored as a probiotic in fermented meats, especially in terms of its effects on fermentation and sensory qualities. Salami-type products were formulated and fermented for 48 h at 32 °C, and then ripening took place at 8 °C for 13 days. pH, titratable acidity, Lactobacillus counts, and contaminating microbiota were analyzed during the process. Sensory evaluation was analyzed in the final products. The salami-type formulation served as an effective medium for growing microorganisms, with the populations of starter and probiotic cultures exceeding 10 8 CFU/g after fermentation and ripening for 15 days. The pH of the end products was ~5.1, titratable acidity ~2.5%, and aw ~0.83. During fermentation and ripening, a significant reduction in total mesophilic aerobic bacteria (>7 logs), coliforms, and Staphylococcus aureus (>8-fold reductions) were observed. The sensory evaluation results indicate that the product's attributes are not influenced by the type of bacteria used, as no significant difference was found (p>0.05). The results show that Lactobacillus acidophilus, Lactiplantibacillus plantarum, or their mixture can be used as a starter culture in fermented meat products. Using L. acidophilus, whether alone or in combination, is a viable option that preserves the characteristics of the fermented product and may enhance the benefits of probiotic consumption.